Digital Leadership and Employee Creativity: The Role of Employee Job Crafting and Person-Organization Fit - Zhu, Jian; Zhang, Bin; Xie, Mingxing; Cao, Qiuju (Frontiers in Psychology, 2022)
Industry 4.0 has changed the paradigm in the business practice and business model, and digital technology has brought radical transformations to enterprises. To support this transformation, digital leaders are required to help enterprises transform and lead them to a more promising future. Based on job demands-resources model and person-organization fit theory, this study examines the relationship between digital leadership and employee creativity. Based on a sample of 357 employees from various Chinese companies, this study used SPSS 22.0 and MPLUS 7.0 to examine the hypotheses. The findings indicate the following (a) digital leadership has a positive effect on employee creativity. (b) employee job crafting mediate the relationship between digital leadership and employee creativity. (c) person-organization fit positively moderates the relationship between digital leadership and employee job crafting. (d) person-organization fit positively moderates the indirect effect of digital leadership on employee creativity via employee job crafting. The findings reveal the effect mechanism of digital leaders on employee creativity and enrich the literature on antecedents of employee creativity. Practical implications and future research are also discussed.